Effects of Polyethylene Glycol on Renal Functional Parameters in Rats - Rafiq, Kazi; Mori, Hirohito; Sherajee, Shamshad J; Kobara, Hideki; Nishiyama, Noriko; Nishiyama, Akira (Journal of Bangladesh Society of Physiologist, 2016)
Background: The use of polyethylene glycol (PEG) is increasing day by day in various purposes by pharmaceutical industries as well as its anti-colonic cancer effects in clinical diseases. Objective: To evaluate the effects of PEG on renal functional and morphological parameters in rats. Methods: Six weeks age matched Sprague-Dawley rats were treated with either vehicle (2 mL of 5% dist. water in saline/kg, i.p. twice daily, n=6), or PEG 400 (2 mL of 5% PEG 400 in saline/kg, i.p. twice daily, n=6). After three weeks treatment all rats were subjected to uninephrectomy (UNX) and continued the treatment for further two weeks. Unpaired t test was used for statistical significance. Results: Before and after uninephrectomy intraperitoneal injection of PEG 400 did not alter systolic blood pressure, renal blood flow, body weight gain and twenty-four hours urine protein excretion rate compared to control rats, however, three weeks after UNX urine protein excretion rate were increased in both groups and was not significant. Intraperitoneal PEG 400 treatment significantly increased twenty-four hours water intake and urine volume compared to control rats. Histopathological evaluation of renal section by periodic acid Schiff staining, Massens trichrom staining and desmin staining did not show any morphological changes compared to control rats. Conclusion: Renal functional and morphological status did not show significant alterations after intraperitoneal injection of PEG for three weeks of uninephrectomized rats. Therefore, present finding suggested that PEG 400 may not have any adverse effects on renal functional as well as morphological parameters in rat. Bangladesh Soc Physiol. 2015, December; 10(2): 61-66